Body weight and lifestyle changes under the COVID-19 pandemic in Japan: a cross-sectional study from NIPPON DATA2010. Issue 11 (30th November 2022) - Taniguchi, Hirokazu; Okuda, Nagako; Arima, Hisatomi; Satoh, Atsushi; Abe, Makiko; Nishi, Nobuo; Higashiyama, Aya; Suzuki, Harumitsu; Ohkubo, Takayoshi; Kadota, Aya; Miura, Katsuyuki; Ueshima, Hirotsugu; et al.
Abstract : Objectives: The COVID-19 pandemic has had an impact on people's lifestyles such as causing body weight changes. This study examined associations among lifestyle changes and body weight during the COVID-19 pandemic among the Japanese population. Design: A cross-sectional study. Setting: A nationwide survey of the general Japanese population. Participants: Total participants were 2244 men and women, of which 911 young/middle-aged (30–69 years old) and 899 older adults (70 years and older) were analysed separately. Outcome: Changes in lifestyle (physical activity, dietary habits and alcohol intake) and body weight during the first wave of COVID-19 in spring 2020. Results: Under the COVID-19 pandemic, 24.1% and 10.1% of Japanese respondents reported weight gain and reduction, respectively. Multivariable-adjusted stepwise logistic regression analyses revealed that the young/middle-aged respondents in the group increased body weight, weight gain was significantly associated with decrease in physical activity (OR 4.01, 95% CI 2.83 to 5.69) and both increase (OR 5.82, 95% CI 3.85 to 8.80) and decrease (OR 2.73, 95% CI 1.52 to 4.93) in eating between meals. In the group that decreased body weight, body weight reduction was significantly associated with increase in physical activity (OR 3.66, 95% CI 1.94 to 6.90), decrease in eating between meals (OR 5.97, 95% CI 3.11 to 11.48) and both increase and decrease in alcohol intake in the young/middle age. For the older adults, body weight gain was higher in women than in men, and significantly associated with higher quartile of regional COVID-19 infection, decrease in physical activity (OR 2.98, 95% CI 1.98 to 4.49), increase in home-cooked meals and increase in eating between meals (OR 4.22, 95% CI 2.55 to 6.99). On the other hand, body weight reduction was significantly associated with decreases in physical activity (OR 2.63, 95% CI 1.62 to 4.27), home-cooked meals and eating between meals (OR 1.95, 95% CI 1.05 to 3.61) in the older adults. Conclusion: Changes in physical activity and eating between meals were associated with body weight change under the COVID-19 pandemic among Japanese.